PENGARUH TELEPHONE OPERATOR TERHADAP KEPUASAN TAMU DI HOTEL SINTESA PENINSULA MANADO - Merry Adrah; Agus Walansendow (Jurnal Hospitaliti, 2023)
The Effect of Telephone Operators on Guest Satisfaction at the Sintesa Peninsula Hotel Manado. The importance of Telephone Operators can be seen in the expression that they are the spearhead of the company, because Telephone Operators play a role as a mouthpiece between the hotel and outsiders. Its main task is to provide fast, friendly and courteous service to all parties who need telephone services. The voice must be in good rhythm and the words spoken must be clear, the intonation of the voice is full of friendliness and attention and always concentrate every time you speak. This study aimed to explain the general duties of telephone operators and to analyze how much influence the performance of telephone operator employees has on the standard operating procedures and job desks of telephone operators. In this study, the techniques used were observation, questionnaire and interview. The final results of the study after analyzing simple linear regression were Ŷ= 5.38 + 0.67X indicating that each increase in one unit of variable X (Telephone Operator Employee Performance) will cause a change in the increase in variable Y (Guest Satisfaction) of 0.67 as well on the contrary. The coefficient of determination r2 = 0.43 or 18.49%. This shows that the variation in the Telephone Operator Employee Performance variable caused by Guest Satisfaction is 18.49%.